Strategi Pembelajaran Tanpa Kekerasan - Muhammad Idrus (Islamic University of Indonesia, 2011)
This paper will discuss learning strategy models which put student as subject of learning. Teacher is expected to take an advantage in using those models to reduce violence in education circumstance. As found in researches and mass media, violence in education circumstances, which is performed by teachers or students, still become high concerns among parents, teachers, and students themselves. One such thing that may cause this violence is learning and teaching approach or strategy by which teachers use. Changing learning and teaching strategy to be more effective and fun will probably reduce those sort of violence in education circumstances, like in schools or universities. The individual character of teachers and students are also discussed in this paper to find other factors of violence in education.